2014
DOI: 10.7461/jcen.2014.16.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness and Functional Outcome in Acute Ischemic Stroke

Abstract: ObjectiveArterial stiffness is a common change associated with aging and can be evaluated by measuring pulse wave velocity (PWV) between sites in the arterial tree, with the stiffer artery having the higher PWV. Arterial stiffness is associated with the risk of stroke in the general population and of fatal stroke in hypertensive patients. This study is to clarify whether PWV value predicts functional outcome of acute ischemic stroke.MethodsOne hundred patients were enrolled with a diagnosis of acute ischemic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Increased plasma concentrations of fibulin 1 are predictive of cardiovascular mortality in type 2 diabetes [18], and a recent study found that common polymorphisms in the FBLN1 gene predict aortic stiffness in young healthy subjects [33]. Aortic stiffness is an important independent risk factor for IS, suggesting the potential usefulness of fibulin 1 as a biomarker [34].…”
Section: Discussionmentioning
confidence: 99%
“…Increased plasma concentrations of fibulin 1 are predictive of cardiovascular mortality in type 2 diabetes [18], and a recent study found that common polymorphisms in the FBLN1 gene predict aortic stiffness in young healthy subjects [33]. Aortic stiffness is an important independent risk factor for IS, suggesting the potential usefulness of fibulin 1 as a biomarker [34].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, baPWV, rather than carotid-femoral PWV (cfPWV) which represents the gold standard among the PWV parameters and reflects the stiffness of central artery, was used to assess arterial stiffness. However, recent studies showed that baPWV was significantly and positively associated with cfPWV, and that both PWV values were similarly associated with cardiovascular risk factors and clinical events (Lee et al, 2014). In addition, PWV and the augmentation index (AI) are the 2 major non-invasive methods of assessing arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged exposure to such conditions can lead to endothelial dysfunction and atherosclerosis 60. Arterial stiffness is a commonly encountered complication of DM, which is also associated with poor functional outcome after stroke 61. DM‐induced oxidative stress and inflammatory responses in turn accelerate atherosclerosis 62.…”
Section: Vascular Impairment In Diabetic Strokementioning
confidence: 99%
“…60 Arterial stiffness is a commonly encountered complication of DM, which is also associated with poor functional outcome after stroke. 61 DM-induced oxidative stress and inflammatory responses in turn accelerate atherosclerosis. 62 Impaired vasodilation leads to prolonged CBF decrease, which can trigger neuronal cell death.…”
Section: Vascular Impairment In Diabetic Strokementioning
confidence: 99%